The synthesis of higher alcohols from CO2 hydrogenation over Mn-Cu-K modified Fe5C2 and CuZnAlZr tandem catalysts - Huang, Jiamin; Zhang, Guanghui; Wang, Mingrui; Zhu, Jie; Ding, Fanshu; Song, Chunshan; Guo, Xinwen (Frontiers in Energy Research, 2023)
The catalytic production of higher alcohols (HAs) is a promising path for converting CO2 into value-added chemical products. The application is still limited by the low selectivity of HAs (less than 10%) on most catalysts. Here, we report a tandem catalyst consisting of Mn-Cu-K modified iron carbide and CuZnAlZr catalyst. The modification of iron carbide with Mn, Cu and K promoters improves the formation of HAs (13.5% Sel.), and the construction of tandem catalysts with CuZnAlZr can further enhance the catalytic performance. By examining different catalyst filling methods and the filling ratio of the tandem catalyst, it was found that the powder mixing resulted in a higher selectivity of HAs with a mass ratio of the two components of 1:1, and a synergistic effect leads to a higher selectivity of HAs (15.5%) with about 40% of propanol and butanol among HAs.